FBXW5 blunts RIGI/MDA5-IFN signaling to drive immunoevasion and chemo-immune resistance in triple-negative breast cancer models - Xin Li; Tong Chen; Wenjing Zhao; Jiaxing Li; Yifan Shang; Bing Chen; Lijuan Wang; Ning Zhang; Xiaoli Kong; Yiran Liang; Yaming Li; Chen Li; et al. (Journal of Clinical Investigation, 2026)
Triple-negative breast cancer (TNBC), characterized by aggressive behavior and poor prognosis, presents a formidable clinical challenge. Despite guideline endorsement of chemoimmunotherapy as a standard treatment in TNBC, durable responses remain rare, largely due to an immunologically “cold” tumor microenvironment (TME). Through integrated analysis, we identified the F-box protein FBXW5 as a tumor-intrinsic immunosuppressive regulator, whose expression is elevated in immunologically “cold” TNBC and correlates with dismal patient survival. Genetic knockdown of murine Fbxw5 suppressed tumor growth, reinvigorated CD8+ T cell-mediated antitumor immunity, and sensitized TNBC tumors to both single-agent and combined chemo-immune therapy in preclinical models. Mechanistically, FBXW5 acts within the SKP1/CUL1/F-box protein (SCF) E3 ligase complex to bind RIGI and MDA5, promoting their K27-linked polyubiquitination and subsequent SQSTM1-mediated autophagic degradation. This process blunts cytosolic RNA sensing and type I interferon (IFN-I) signaling, thereby limiting CD8+ T cell infiltration and activation. Our findings establish FBXW5 as a master regulator of the “cold” TME, presenting a potential predictive biomarker and actionable therapeutic target for enhancing chemoimmunotherapy in TNBC.